1990
DOI: 10.1017/s0022112090003494
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillary convection in long horizontal layers of low-Prandtl-number melts subject to a horizontal temperature gradient

Abstract: Thermocapillary convection arising in small-depth layers (long horizontal cavities) subject to a horizontal temperature gradient is studied numerically. A broad range of values of the Reynolds-Marangoni number, Re, is considered for three values of the aspect ratio (A = length/height). For the largest aspect ratio considered, A = 25, the fully developed Poiseuille-Couette solution is reached, but only for moderate Re. The limiting Re value for the observability of such a fully developed solution is derived as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…Laure and Roux [6], Ben Hadid and Roux [7] considered thermocapillary and buoyancy e¤ects in liquids with a small Prandtl number ðPr < 1Þ. Later on, Gershuni et al [8] found steady rolls in the case of conducting surfaces for Pr > 1.…”
Section: Introductionmentioning
confidence: 99%
“…Laure and Roux [6], Ben Hadid and Roux [7] considered thermocapillary and buoyancy e¤ects in liquids with a small Prandtl number ðPr < 1Þ. Later on, Gershuni et al [8] found steady rolls in the case of conducting surfaces for Pr > 1.…”
Section: Introductionmentioning
confidence: 99%
“…We consider a two-dimensional rectangular cavity with aspect ratio A, where A = L/H, and L is length and H hight as shown in Fig.1 Ov Re OT cOxGrl/2 cOy (4) and other conditions on the horizontal boundaries are…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…While, for adiabatic surfaces, Parmentier et al [9] found that unsteady disturbances in the form of oblique waves are the most unstable. Furthermore, Ben Hadid and Roux [10][11][12] numerically studied the two-dimensional thermocapillary and thermocapillary-buoyant convection of fluid in an open cavity with various aspect ratios, and showed the existence of a multicellular steady flow and a transition from steady to oscillatory flow. Mundrane and Zebib [13] analyzed the onset of oscillatory flow for thermocapillary-buoyant convection, and found that a transition of steady state flow to unsteady flow occurs as soon as the Grashof number exceeds a lower bound value.…”
Section: Introductionmentioning
confidence: 99%